Pengaruh Penerapan Sistem Akuntansi Keuangan Pemerintah Daerah dan Sistem Pengendalian Internal terhadap Kualitas Laporan Keuangan Daerah dengan Kompetensi Sumber daya Manusia sebagai Variabel Moderasi - Sabbrina, Windy; Putri, Sri Yuli Ayu; Bustari, Andre (Jurnal Riset Akuntansi, 2024)
This research aims to determine the effect of implementing regional government financial accounting systems and internal control systems on the quality of regional financial reports with human resource competency as a moderating variable. This research uses quantitative research methods and is primary data. The data source was taken by distributing questionnaires to departments and agencies that are members of regional apparatus organizations in the Agam Regency Government which were selected using a purposive sampling technique. The results of this research indicate that the implementation of the regional government financial accounting system partially has a significant positive effect on the quality of regional financial reports, the internal control system partially has a significant positive effect on the quality of regional financial reports, the implementation of the regional government financial accounting system and the internal control system simultaneously influences the quality Regional financial reports and human resource competency can strengthen the influence of the implementation of regional government financial accounting systems and internal control systems on the quality of regional financial reports.